STUDIES ON BIOACTIVE POTENTIAL OF STREPTOMYCES SPP. (KX710212). ISOLATED FROM ENVIRONMENTAL POLLUTED SAMPLE, RANIPET, VELLORE, INDIA - Geo N, Henita; A, Panneerselvam (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Natural products from bacterial origin played and still play a valuable role in drug discovery and provide diverse health-promoting compounds that help to cure or alleviate serious diseases. Methods: A total of 4 actinobacterial strains were isolated from 2 different environmental polluted soil samples collected from Ranipet, Vellore, Tamil Nadu, India. Of 15 isolates screened for antibacterial property, 4 isolates (PS1, PS2, and PS3) were found potent and characterized phenotypically and genotypically. Results: The 16S rDNA gene sequences of potent strain showed 97% similarity with Streptomyces spp. and termed as Streptomyces sp. The bioactivity was revealed by antibacterial and antioxidant activity. Conclusion: Hence, these findings provide scientific evidence to validate the pharmacological use and have the potential contribution in the discovery of new lead that play a key role in the field of therapeutics. Keywords: Actinomycetes, Bioactive compounds, Antibacterial property.